The Relationship between Teachers' Teaching Style Perceptions and Learning Motivation on Science Learning Outcomes: Hubungan Persepsi Gaya Mengajar Guru dan Motivasi Belajar terhadap Hasil Belajar IPA - Prianti, Rahmawati Antinie; Efendi, Nur (Universitas Muhammadiyah Sidoarjo, 2025)
Background: The low student learning outcomes in science subjects are influenced by both internal and external factors. Student perceptions of teaching styles and learning motivation are crucial external and internal factors, respectively. Aims: This study aims to determine the relationship between student perceptions of teacher teaching styles and learning motivation on cognitive learning outcomes in seventh-grade science at SMP Negeri 1 Bangil. Methods: An ex-post facto correlational design was used with a population of 360 students and a sample of 186 students selected through simple random sampling. Data were analyzed using simple linear and multiple linear regression with SPSS-25. Results: The study found a positive and significant relationship between student motivation and cognitive learning outcomes. While student perception of teacher teaching styles showed a relationship with cognitive learning outcomes, the results of the hypothesis test show a contradiction between the partial and simultaneous findings, where perception of teaching styles was not found to have a significant partial effect but had a significant simultaneous effect when combined with learning motivation. Novelty: This study provides unique insights into the relationship between teaching style perception, motivation, and learning outcomes within the specific context of a junior high school in Bangil, highlighting the need for teachers to develop engaging and motivating learning strategies. Implications: The findings suggest that teachers should develop engaging and motivating teaching strategies to improve student learning outcomes. Future research is needed to explore other factors influencing learning outcomes to provide a more comprehensive understanding. Highlights : The study found a positive and significant relationship between student motivation and cognitive learning outcomes. Student perceptions of teaching styles did not have a significant partial effect on learning outcomes. However, when combined with motivation, perceptions of teaching styles had a significant simultaneous effect on learning outcomes. Keywords: Teacher's Teaching Style, Learning Motivation, Cognitive Learning Outcomes, Science Education, Ex-Post Facto